The silicon p-n-p-n switch and controlled rectifier (thyristor). - Holonyak, N., Jr.
Based on the two-transistor model of Jim Ebers (a p-n-p transistor driving an n-p-n, and the n-p-n driving the p-n-p), the two-terminal and three-terminal Si p-n-p-n switch (low power) originated at Bell Telephone Laboratories (BTL) in 1954-1955. The two-terminal version, with its various limitations (along with tile Si technology supplied by BTL, Moll's group), went with Shockley to the West Coast. The two-terminal device and the Shockley enterprise failed, except as an unplanned, unpredicted transfer of technology that accidentally launched Silicon Valley. The three-terminal p-n-p-n device introduced by GE (1957) as the Si controlled rectifier (SCR, later thyristor) succeeded from the beginning, however, and became the dominant control device in the power industry. The early history of this work (1954-1960), including the shorted-emitter and symmetrical switch (TRIAC), is described. The early work proved the need to employ, besides the basic vertical p-n-p-n layering, lateral p-n patterning and the use of the lateral geometry for three-terminal operation, shorted emitters, symmetrical switches (TRIACs), regenerative gate operation, and ultimately gate-turn-off switches. Indeed, the two-terminal device could not match the performance of the three-terminal p-n-p-n switch, which became the premier megawatt control device of the power industry
Keywords: Jim Ebers; Si; TRIAC; Controlled rectifier; Gate-turn-off switches; Lateral p-n patterning; Power electronics development history; Power industry; Regenerative gate operation; Shorted-emitter.; Silicon p-n-p-n switch; Symmetrical switch; Technology transfer; Thyristor; Two-transistor model; Vertical p-n-p-n layering